2011
DOI: 10.1093/cercor/bhq278
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Aspects of Subplate Zone Studied with Gene Expression in Sauropsids and Mammals

Abstract: There is currently a debate about the evolutionary origin of the earliest generated cortical preplate neurons and their derivatives (subplate and marginal zone). We examined the subplate with murine markers including nuclear receptor related 1 (Nurr1), monooxygenase Dbh-like 1 (Moxd1), transmembrane protein 163 (Tmem163), and connective tissue growth factor (Ctgf) in developing and adult turtle, chick, opossum, mouse, and rat. Whereas some of these are expressed in dorsal pallium in all species studied (Nurr1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 111 publications
6
113
1
Order By: Relevance
“…Subplate cells are some of the earliest generated neurons in cortex (Rakic and Kostovic, 1990; Hoerder‐Suabedissen et al, 2009; Oeschger et al, 2012; Hoerder‐Suabedissen, 2013). These studies strengthen the hypothesis that an embryonic subplate was present in the ancestors of mammals and that additional cellular populations evolved as cortical development and connectivity became more complex (Montiel et al, 2011; Wang et al, 2011a). In the human cortex we observed that subplate subpopulations show increased compartmentalization and that these segregate into sublayers (Hoerder‐Suabedissen and Molnár, 2015).…”
Section: Exploring Brain Evolution From Transcriptome Databasessupporting
confidence: 72%
See 1 more Smart Citation
“…Subplate cells are some of the earliest generated neurons in cortex (Rakic and Kostovic, 1990; Hoerder‐Suabedissen et al, 2009; Oeschger et al, 2012; Hoerder‐Suabedissen, 2013). These studies strengthen the hypothesis that an embryonic subplate was present in the ancestors of mammals and that additional cellular populations evolved as cortical development and connectivity became more complex (Montiel et al, 2011; Wang et al, 2011a). In the human cortex we observed that subplate subpopulations show increased compartmentalization and that these segregate into sublayers (Hoerder‐Suabedissen and Molnár, 2015).…”
Section: Exploring Brain Evolution From Transcriptome Databasessupporting
confidence: 72%
“…While these divisions share a common basic plan at early developmental stages, later developmental programs trigger differential gene expression, neurogenetic patterns (Tsai et al, 1981; Nomura et al, 2013), lamination (Medina and Reiner, 2000), connectivity (Aboitiz et al, 2002; Karten, 2013), and cytoarchitecture (Wang et al, 2010) for each brain compartment. Diversification of the adult brain in gene expression and morphology across vertebrate phylogeny makes comparisons difficult (Aboitiz and Montiel, 2007; Wang et al, 2011a; Belgard and Montiel, 2013). The cerebral hemispheres of vertebrates show enormous diversity, having differences in size and complexity distinct for each clade (Jarvis et al, 2005, 2013; Aboitiz and Montiel, 2007).…”
Section: Comparisons Between Forebrain Organization In Mammals and Samentioning
confidence: 99%
“…In the developing neocortex of mammals, (i) an SVZ is present, (ii) the main afferents enter the CP from beneath it, (iii) a separate SP layer is present, (iv) the CP forms in an inside-out fashion, and (v) supragranular cells are present. By contrast, in the developing dorsal pallium of sauropsids, (i) there is no SVZ (15,16), (ii) the main afferents seem to enter the CP from above it (42,43), (iii) there does not seem to be a separate SP layer (44), (iv) the CP forms in an outside-in fashion (15,16), and (v) no equivalent of the supragranular cells of mammals seems to exist (45,46). Interestingly, the migratory defect of chicken MGE cells that prevented them from entering the neocortical CP/MZ (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Despite intensive research in various mammalian species in the last 40 y (reviewed in refs. [5][6][7][8][9][10][11], the origin as well as evolutionary and developmental mechanisms that underlie the extraordinary expansion and regional diversification of the SP in human are not well understood (10,12).…”
mentioning
confidence: 99%